Teacher Strategies in Integrating Character Values into Learning - dian hikmayana; sahri; Mohd Izzuddin Mohd Pisol (International Journal of Education and Learning, 2026)
The main problem is that the integration of character education into classroom learning has not been implemented optimally, as many teachers still face challenges in consistently integrating character values into the teaching and learning process. This research aims to analyze teacher strategies in integrating character values into the learning process. The background of this study lies in the urgency of character education in schools, where teachers are expected not only to transfer knowledge but also to foster moral values among students. Using a qualitative approach with a case study design, the research involved teachers, students, and school principals as key informants. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using Miles and Huberman’s interactive model consisting of data reduction, display, and conclusion drawing. The findings indicate that teachers employ three main strategies in integrating character values: embedding values within the curriculum, implementing interactive and participatory learning methods, and habituating values through daily classroom activities. These strategies contribute significantly to developing students’ discipline, responsibility, respect, and cooperation. However, the study also highlights several challenges such as limited teacher competence, lack of institutional support, and insufficient parental involvement. The research emphasizes that effective character education requires comprehensive collaboration among teachers, schools, parents, and communities. It concludes that character-based learning is a strategic instrument for fostering students’ holistic development and promoting a more ethical and inclusive school culture.